Befriending and Re-ablement Service: a better alternative in an age of austerity. Issue 1 (14th March 2017) - McGoldrick, Chris; Barrett, Giles Andrew; Cook, Ian
Abstract : Purpose: The purpose of this paper is to share the findings of a research evaluation into a Befriending and Re-ablement Service (BARS) which offers a host of positive outcomes such as reduced loneliness and keeping as well as possible for a growing segment of the world's population. The recent increase in longevity is one of humanity's great success stories. But ageing comes at a price, and decision takers worry about the stresses and strains of an ageing society. Design/methodology/approach: Following a literature review, this paper presents the findings of an evaluation of an alternative innovative form of support for older people, namely BARS, that has been developed on Merseyside. Semi- and unstructured interviews were carried out with stakeholders including service users and carers. A cost-benefit analysis is also reported. Finally the theoretical and policy implications of this research are explored. Findings: Befriending and re-ablement officers is both a socially and economically cost effective means of enhancing independent living among older people, reducing loneliness and isolation that can contribute to ill health. The research shows that funding for the BARS scheme should be sustained and expanded, despite or because of the current era of cutbacks in UK and international service provision. Originality/value: The paper highlights the value, role and importance of both befriending and re-ablement in a time of acute public and voluntary sector funding pressures. The paper is of value to a range of stakeholder groups such as older people, local and central governments and health care commissioners.